Development of Ti-12Mo-8Nb alloy for biomedical application - Gabriel, Sinara Borborema; da Silva Kassya, Jessica Peixoto; Jacinto, Caroline Miranda; dos Santos, Leizy Pâmela Oliveira; Nunes, Carlos Angelo [UNESP]; Araújo, Leonardo Sales; Dille, Jean; Baldan, Renato; de Almeida, Luiz Henrique (Trans Tech Publications, 2017)
Several beta titanium alloys were developed for biomedical applications due to the combination of low elasticity modulus, high strength, fatigue resistance and good ductility with excellent corrosion resistance. In this regard, a new metastable beta titanium Ti-12Mo-8Nb alloy was developed, as an alternative for the traditional Ti-6Al-4V alloy, with the substitution of vanadium and aluminum for molybdenum and niobium. The objective of this work was to present the microstructural characterization and mechanical properties of the Ti-12Mo-8Nb alloy, heat treated for 1h at 950ºC under high vacuum and then water quenched. The microstructure of the alloy was characterized by X-ray diffraction and optical microscopy. Vickers microhardness and nanoindentation were performed for determination of hardness, Young’s modulus and the ratio of hardness to Young’s modulus. The Ti-12Mo-8Nb microstructure consisted of β phase and the values obtained for the ratio of hardness to Young’s modulus were higher than the Ti-6Al-4V alloy.
Keywords: Biomaterials; Microstructure; Properties; Ti alloys; Ti-Mo-Nb alloys